[OP.LB.02.01] STRATEGY TO OPTIMIZE SODIUM INTAKE FOR INDIVIDUAL PATIENTS. (September 2016) - Alderman, M.; McCarron, D.; Graudal, N.
Abstract : Objective: Most Americans (90%) have dietary sodium intakes between 2.5 and 5.0 g/d. These limits are coterminous with optimal Cardiovascular (CVD) outcomes and, outcomes do not vary within this range. Beyond those limits, CVD risk increases. The health consequences of raising low, or lowering high intakes, is unknown. Thus, for persons at the extremes of sodium intake, we propose a strategy for their identification, dietary remediation, and ongoing health assessment may benefit as much as10% of the nation's population. Design and method: Epidemiological studies linking sodium intake with subsequent CVD were reviewed. History, physical exam, urine and blood tests can identify patients with sodium intakes < 2.5, and > 5.0 g/d. Dietary modification and/or supplementation can alter sodium intake. Although the strategy proposed is experimental, because its components are safe, and its effects readily assessed, it can be safely applied in clinical settings pending feasible rigorous scientific testing. Results: Persons with sodium intake < 2.5 or > 5. g/d can be identified and treated. Restricted diets and elevated Plasma Renin Activity (PRA), or signs of volume depletion, are associated with low sodium intakes < 2.5. Increased CVD risk is also present at sodium intakes >5.0 g/, but only when associated with hypertension. These patients have suppressed PRA. Sequential spot and, finally, 24-hour urine-analyses, can identify those most likely to benefit from optimtimizing sodium intake through a 1.0 g/d dietary change. Urinary sodium, PRA and blood pressure response should be monitored. Randomized trials – ultimately with hard clinical endpoints - must validate these interventions. Conclusions: The sodium intake of most Americans is optimal, yet 10% with intakes <2.5 or >5.0 g/d are at increased CVD risk. Since health consequences of altering dietary sodium are unknown, any intervention to modify intake is experimental and can and should be evaluated through clinical trials. Nevertheless, concerned and informed patients and physicians may seek to improve health outcomes by increasing or decreasing their sodium intakes. We have described a feasible strategy to identify individual patients for whom proven intervention to optimize sodium intake may be beneficial.